Jolanta Dybała, Ideał kobiety w pismach kapadockich Ojców Kościoła i Jana Chryzostoma, Byzantina Lodziensia 14, Łódź 2012, Wydawnictwo Uniwersytetu Łódzkiego, ss. IX + 482. - Kochanek, Piotr (Vox Patrum, 2012)
nie dotyczy